Concentración espermática de semen porcino (sus scrofa var. domesticus) mediante metodologías aplicadas comercialmente en la parroquia Conocoto del cantón Rumiñahui - Tana Arcos, Henry Rodrigo (2017)
The study was carried out at the Artificial Insemination Center "Suis Genetic" located in the Conocoto parish, Rumiñahui, during the months of December 2016 to April 2017. The objective of the study was to determine the seminal quality and sperm concentration of porcine semen (Sus scrofa var. Domesticus) using three commercially used methodologies (Neubauer chamber, Karras Densimeter and Colorimeter). A completely randomized design (DCA) was used with three treatments (Neubauer, Karras and Colorimeter) and six replicates (weeks), arranged in factorial arrangement 2 x 3. The variables evaluated were color, pH, volume, mass motility, individual motility and sperm concentration. The results showed that the ejaculates presented a milky white (concentrated) color in paternal line (LP) and maternal line (LM) with a characteristic smell (sui generis) for the two lines, considered as normal parameters. The volume that was obtained was between 180 to 200 mL for LP and LM with a pH of 7.5 in LP and LM, which is a neutral value and considered normal. As for the mass motility for LP and LM, it was found to be between 80-85% (rapid eddies), considered to be very good. While the individual motility for LP and LM was between 4 to 5 (fast progressive movements), respectively. When analyzing the concentration by genetic line, the LM presented a higher concentration with 511.53 x 106 esper / ml and LP with 512.47 x 106 esper / ml, these results being statistically not significant. In contrast, when analyzing the Colorimeter method, the highest value (532.5 x 106 esper / ml) and Nuebauer the lowest value (499.75 x 106 esper / ml) were obtained, determining that the values were not statistically different. Within the economic analysis it was concluded that the most economical method was the Karras system followed by Colorimeter and Burker, but the Colorimeter was the method with the highest net benefit.